A Chinese cross-sectional study on depression and anxiety symptoms in patients with psoriasis vulgaris. Issue 3 (16th March 2019) - Tian, Zhen; Huang, Yike; Yue, Tao; Zhou, Jiaqing; Tao, Lu; Han, Ling; Yan, Kexiang; Huang, Qiong; Zhang, Zhenghua; Shao, Chunhong
ABSTRACT: Previous studies have reported a higher incidence of depression and anxiety in psoriasis patients compared to the general population, which has important implications for assessment and treatment. In this study, we determined the frequency of depression and anxiety in Chinese patients with psoriasis and its relationship with disease severity and other demographic variables. The study included 208 Chinese patients with psoriasis vulgaris. The Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder scale (GAD-7) were used to screen for depression and anxiety. The Psoriasis Area and Severity Index (PASI) was used to assess the severity of psoriasis. Of the 208 patients included in the study, 29 patients (13.9%) were positive for moderate-to-severe depression (PHQ-9 ≥ 10) and 22 patients (10.6%) were positive for anxiety (GAD-7 ≥ 10) symptoms. Both positive stress reactors who perceived stress as an exacerbating factor of psoriasis and moderate-to-severe psoriasis were found to be positive predictors for the presence of moderate-to-severe depression or anxiety symptoms while longer duration and late onset age played a protective role. In the sample of Chinese patients with psoriasis there was a clinically significant prevalence of depression and anxiety. Our study suggests that Chinese psoriasis patients should be screened for psychiatric comorbidities.